On the Personality of Convict - BAISALOV, Ali Dzhumamuratovich; BISSENOVA, Meruert Kylyshbayevna; ILYASOVA, Bakytgul; ARATULY, Kuanysh; KUSMAMBETOV, Kuanysh Daniyarovich (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
The article deals with the issues of the convict’s personality. The authors tried to explore this problem in detail through the dialectical approach. A special attention was paid to the issues of convict’s personal change under the conditions of institutional confinement. The authors make accurate conclusions regarding the impossibility of depicting convicts’ profiles without focusing on their moral and ethical as well as psychological peculiarities. In recent years, the state penal policy has undergone significant changes. In this regard, the reform of the penitentiary system, improvement and optimization of the penal law and the penal system required greater attention to the individual characteristics of the convicted to imprisonment. The current legislation is determined that the funds are used, and the direction, taking into account personal characteristics and features of the behavior of prisoners. In the last few years a number of authors emphasized the role of learning and psychological correction of personality characteristics and features of the behavior of prisoners to prevent destructive phenomena in prisons, enabling adaptation to life after release from punishment, the prevention of recidivism. In this aspect of the study of character traits of the person convicted it is very relevant, as the character is seen in the domestic and foreign psychology as one of the most important components of personality that determines human behavior and activity.